GAMBARAN KARAKTERISTIK SUMUR WARGA DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU KOTA SEMARANG - Insani Nashiroh; M. Sakundarno Adi; Lintang Dian Saraswati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Escherichia coli is the indicator for water pollution including in well water. Well water that is ineligible can be contaminated by Escherichia coli. This study aims to describe the characteristic of well in Kedungmundu Health Center. This study uses cross-sectional design. The sample for this study is 97 well that taken by simple random sampling technique. The most well is dug well (59,8%), lined well (61,9%), and covered well (81,4%); well within ≥10 meter in distance with latrine (61,9%) and septic tank (67%); well  within <10 meter in distance with sewage (67%); well with absence of  dumpsite (78,4%) and livestock pen (81,4%) within <10 meter in distance. This result shows that most of well is eligible according to Indonesia Health Ministry. It is recommended doing a laboratory test of well water to know the presence of bacteria.